2018
DOI: 10.3390/su10030593
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of Urban Expansion along the Guangzhou–Foshan Inter-City Rail Transit Corridor, China

Abstract: Understanding the urban expansion process along inter-city rail transit corridors is critical to regional integration of city groups. Though numerous studies have considered the influences of rail transit on land use and urban form, most have focused on local station areas or intra-city urban structures. Few studies have examined the effects and dynamic process along inter-city rail transit corridors at a regional scale. In this study, multi-remote sensing images, landscape metrics and gradient analysis were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…The results indicate that transportation connection had high contributions to the dynamic patterns of urban expansion. This was consistent with the results reported for Jiuquan City (Xie, Gong, Sun, Gou, & Xie, ), Beijing City (Mo, Wang, Zhang, & Zhuang, ; Zhao, Zheng, Yuan, & Zhang, ), and Foshan City (Li et al, ) in China.…”
Section: Discussionsupporting
confidence: 92%
“…The results indicate that transportation connection had high contributions to the dynamic patterns of urban expansion. This was consistent with the results reported for Jiuquan City (Xie, Gong, Sun, Gou, & Xie, ), Beijing City (Mo, Wang, Zhang, & Zhuang, ; Zhao, Zheng, Yuan, & Zhang, ), and Foshan City (Li et al, ) in China.…”
Section: Discussionsupporting
confidence: 92%
“…A large number of the world's population has settled in urban areas; this figure is projected to increase to approximately 6.3 billion by 2050 [1]. Due to city-centered regional development and industrialization, the spatial evolution of urban land will be characterized by alternating processes of diffusion and coalescence, which will inevitably lead to urban agglomeration [2,3]. Urban agglomerations, also defined as megalopolises or metropolitan areas, are an advanced form of spatial organization for cities, characterized by contiguous areas of constantly developed urban territories with increasing economic interconnection [4].…”
Section: Introductionmentioning
confidence: 99%
“…These studies analyzed urban structure or changes in land use near transit stations; however, research on the integration characteristics of urban agglomeration along an inter-city rail network are rare. Li et al analyzed the spatial heterogeneity and urban structural changes along the Guangzhou-Foshan inter-city rail network, revealing the metropolitan coalescence process and the significant impact of rail transit on urban expansion at the urban fringes [2]. However, their research did not consider the interactions between landscape ecology and urban agglomerations along the inter-city rail transit corridor.…”
Section: Introductionmentioning
confidence: 99%
“…The development of Light Rail Transit systems (LRTs) can be divided into four stages, namely the pre-planning, planning, construction, and operation stages [18,23,55]. Time series of remote sensing images are helpful for monitoring land use changes over different periods.…”
Section: Assessing the Impacts Of Lrts On Surrounding Urban Land Usementioning
confidence: 99%
“…To assess the impacts of LRT development on surrounding urban land use, we also need to build a two-sided buffer because LRTs mainly exert impacts on land use within a certain proximity [23,24,26]. Previous studies related to the cases in Chinese cities have indicated that a 2 km buffer is quite suitable for quantifying the LRT impacts on land use [13,14,55]. Nevertheless, such impacts may vary significantly across regions, economic zones, and policy regime, and we should analyze the gradual transition of land use changes to better determine the buffer size.…”
Section: Assessing the Impacts Of Lrts On Surrounding Urban Land Usementioning
confidence: 99%